Nano- and Macroscale Study of the Lubrication of Titania Using Pure and Diluted Ionic Liquids - Cooper, Peter K.; Staddon, Joe; Zhang, Songwei; Aman, Zachary M.; Atkin, Rob; Li, Hua (Frontiers in Chemistry, 2019)
Titanium is a strong, corrosion-resistant light – weight metal which is poised to replace steel in automobiles, aircraft, and watercraft. However, the titanium oxide (titania) layer that forms on the surface of titanium in air is notoriously difficult to lubricate with conventional lubricants, which restricts its use in moving parts such as bearings. Ionic liquids (ILs) are potentially excellent lubricants for titania but the relationship between IL molecular structure and lubricity for titania remains poorly understood. Here, three-ball-on-disk macrotribology and atomic force microscopy (AFM) nanotribology measurements reveal the lubricity of four IL lubricants: trioctyl(2-ethylhexyl)phosphonium bis(2 ethylhexyl)phosphate (P8,8,8,6(2) BEHP), trihexyl(tetradecyl)phosphonium bis(2 ethylhexyl)phosphate (P6,6,6,14 BEHP), trihexyl(tetradecyl)phosphonium bis(2,4,4 trimethylpentyl)phosphinate (P6,6,6,14 (iC8)2PO2), and trihexyl(tetradecyl)phosphonium bis(trifluoromethylsulfonyl)imide (P6,6,6,14 TFSI). The macrotribology measurements demonstrated that friction decreased in P6,6,6,14 TFSI by four times (μ = 0.13) compared to in hexadecane, even at 60 °C and loads up to 10 N. On the other hand, P8,8,8,6(2) BEHP reduced friction most effectively in the AFM nanotribology measurements. The results were interpreted in terms of the lubrication regime. The lower viscosity of P6,6,6,14 TFSI coupled with its good boundary lubrication made it the most effective IL for the macrotribology measurements, which were in the mixed lubrication regime. Conversely, the cation structure the P8,8,8,6(2) BEHP allowed it to adsorb strongly to the surface and minimized energy dissipation in the nanotribology measurements, although its high bulk viscosity inhibited its performance in the mixed regime. These results reinforce the importance of carefully selecting IL lubricants based on the lubrication regime of the sliding surfaces.